2016
DOI: 10.1055/s-0042-107673
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial Activity of a Calophyllum brasiliense Leaf Extract

Abstract: (Clusiaceae) is a tree that grows mainly in the Atlantic Forest in Brazil. Its leaves possess antibacterial activity, cytotoxic activity against certain tumor cell lines, and antimicrobial activity in BALB/c mice infected with .Aiming to identify ultrastructural changes and DNA fragmentation in promastigotes were treated with a concentration of the dichloromethane extract and coumarin (-) mammea A/BB from leaves that inhibited 50 % of the parasites (IC), and were evaluated by transmission and scanning electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…C. brasiliense plant is a folk medicine used in many infections, such as leishmaniasis [ 10 13 ], in Brazil and other countries [ 9 13 , 17 27 ]. In the present study, we showed anti- Leishmania activity and immunomodulatory effects of C. brasiliense during infection.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…C. brasiliense plant is a folk medicine used in many infections, such as leishmaniasis [ 10 13 ], in Brazil and other countries [ 9 13 , 17 27 ]. In the present study, we showed anti- Leishmania activity and immunomodulatory effects of C. brasiliense during infection.…”
Section: Resultsmentioning
confidence: 99%
“…The product of this evaporation, a dark green water-insoluble residue, was dissolved in dichloromethane. The organic solvent was then removed by evaporation at room temperature, and the obtained hydroalcoholic extract (≈75.0 g) was stored at −10°C, protected from light until use [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations